2020
DOI: 10.1002/nop2.565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a person‐centred and thriving‐promoting intervention on nursing home staff job satisfaction: A multi‐centre, non‐equivalent controlled before–after study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Treweek (2015) described that "the more the intervention requires health professionals and patients to do, the more difficult it will be to recruit and retain participants" & McCance, 2016;van den Pol-Grevelink et al, 2012). This was not found in the present study, which agrees with a recent study conducted by Vassbø et al (2020). However, the results showed a variation in the distribution of how the NAs rated their job satisfaction, implying heterogeneity within the group.…”
Section: Discussionsupporting
confidence: 82%
“…Treweek (2015) described that "the more the intervention requires health professionals and patients to do, the more difficult it will be to recruit and retain participants" & McCance, 2016;van den Pol-Grevelink et al, 2012). This was not found in the present study, which agrees with a recent study conducted by Vassbø et al (2020). However, the results showed a variation in the distribution of how the NAs rated their job satisfaction, implying heterogeneity within the group.…”
Section: Discussionsupporting
confidence: 82%
“…The lack of significant results over time can also be found in the floor and ceiling effects (Vassbø et al, 2020;Wolf et al, 2008).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The lack of significant results over time can also be found in the floor and ceiling effects (Vassbø et al, 2020; Wolf et al, 2008). These effects arise when the scoring is already so high or low that an improvement is hardly possible.…”
Section: Introductionmentioning
confidence: 99%
“…Although PCC should theoretically improve healthcare professional outcomes, the empirical evidence is still unclear. Multiple studies have shown a non‐significant effect of PCC on healthcare professionals in mostly elderly and residential care (Nocon et al, 2019; Schaap et al, 2019; Vassbø et al, 2020). A pilot study was therefore created to research the feasibility of PCC for the improvement of healthcare professional outcomes in hospitals, the initial cross‐sectional results of which are presented here.…”
Section: Introductionmentioning
confidence: 99%